New technologies in the management of risk and violence in forensic settings. (30th April 2015) - Tully, John; Larkin, Fintan; Fahy, Thomas
<x content-type="archive" xml:space="preserve">Abstract</x> Novel technological interventions are increasingly used in mental health settings. In this article, we describe 3 novel technological strategies in use for management of risk and violence in 2 forensic psychiatry settings in the United Kingdom: electronic monitoring by GPS-based tracking devices of patients on leave from a medium secure service in London, and closed circuit television (CCTV) monitoring and motion sensor technology at Broadmoor high secure hospital. A common theme is the use of these technologies to improve the completeness and accuracy of data used by clinicians to make clinical decisions. Another common thread is that each of these strategies supports and improves current clinical approaches rather than drastically changing them. The technologies offer a broad range of benefits. These include less restrictive options for patients, improved accountability of both staff and patients, less invasive testing, improved automated record-keeping, and better assurance reporting. Services utilizing technologies need also be aware of limitations. Technologies may be seen as unduly restrictive by patients and advocates, and technical issues may reduce effectiveness. It is vital that the types of technological innovations described in this article should be subject to thorough evaluation that addresses cost effectiveness, qualitative analysis of patients' attitudes, safety, and ethical considerations.